SYSTEMATIC LITERATURE REVIEW: ENHANCING STUDENTS' DIGITAL LITERACY AND DIGITAL COMPETENCY THROUGH TECHNOLOGICAL INNOVATIONS IN HIGHER EDUCATION - Afrizal; Albert Herlambang; Claudie Tiofanny; Petrus Loo (CV. RADJA PUBLIKA, 2025)
This article explores the enhancement of students' digital literacy and competencies through technological innovation in higher education. Digital transformation has reshaped the way teaching and learning occur, particularly with the implementation of artificial intelligence, virtual reality, and digital learning platforms. This literature review spans research from 2019 to 2023, highlighting the impact of the COVID-19 pandemic, the role of technology in distance learning, and the challenges of integrating technology into educational institutions. The research findings indicate that technological innovation in higher education has the potential to improve students' digital literacy and competencies, although infrastructure challenges and institutional readiness remain significant barriers.